Respuesta :
Answer:
[tex]x->-2^{-}, p(x)->-\infty[/tex] and as [tex]x->-2^{+}, p(x)->-\infty[/tex]
Step-by-step explanation:
Given
[tex]p(x) = \frac{x^2-2x-3}{x+2}[/tex] -- Missing from the question
Required
The behavior of the function around its vertical asymptote at [tex]x = -2[/tex]
[tex]p(x) = \frac{x^2-2x-3}{x+2}[/tex]
Expand the numerator
[tex]p(x) = \frac{x^2 + x -3x - 3}{x+2}[/tex]
Factorize
[tex]p(x) = \frac{x(x + 1) -3(x + 1)}{x+2}[/tex]
Factor out x + 1
[tex]p(x) = \frac{(x -3)(x + 1)}{x+2}[/tex]
We test the function using values close to -2 (one value will be less than -2 while the other will be greater than -2)
We are only interested in the sign of the result
----------------------------------------------------------------------------------------------------------
As x approaches -2 implies that:
[tex]x -> -2^{-}[/tex] Say x = -3
[tex]p(x) = \frac{(x -3)(x + 1)}{x+2}[/tex]
[tex]p(-3) = \frac{(-3-3)(-3+1)}{-3+2} = \frac{-6 * -2}{-1} = \frac{+12}{-1} = -12[/tex]
We have a negative value (-12); This will be called negative infinity
This implies that as x approaches -2, p(x) approaches negative infinity
[tex]x->-2^{-}, p(x)->-\infty[/tex]
Take note of the superscript of 2 (this implies that, we approach 2 from a value less than 2)
As x leaves -2 implies that: [tex]x>-2[/tex]
Say x = -2.1
[tex]p(-2.1) = \frac{(-2.1-3)(-2.1+1)}{-2.1+2} = \frac{-5.1 * -1.1}{-0.1} = \frac{+5.61}{-0.1} = -56.1[/tex]
We have a negative value (-56.1); This will be called negative infinity
This implies that as x leaves -2, p(x) approaches negative infinity
[tex]x->-2^{+}, p(x)->-\infty[/tex]
So, the behavior is:
[tex]x->-2^{-}, p(x)->-\infty[/tex] and as [tex]x->-2^{+}, p(x)->-\infty[/tex]